Determinant Determinan Perilaku Bidan dalam Penerapan Kewaspadaan Standar pada Pelayanan Kontrasepsi Implan di Kabupaten Karawang: Determinants of Midwife Behavior in the Prevention of Standard Implant Contraception Service in KB Safari Activities in Karawang Districtontraception Service in KB Safari Activities in Karawang District - Warliana warliana (Jurnal Asuhan Ibu dan Anak, 2019)
Abstract One effort used to improve the quality of family planning services is to ensure the use of standard family planning services for health workers including prevention of infection. The results of the 2015 SUSENAS illustrate the high number of modern MKJP Contraception users at 58.99%, with the Government KB clinic as a health facility providing the most family planning services at 66.40%. One of the efforts to support the increase in users of implant and IUD contraception in Karawang District was carried out by one of them through the District KB Safari. The research objective was to determine the determinants of midwives' behavior in the application of infection prevention in implant contraceptive services carried out in KB family planning activities, including variables of knowledge, attitudes, facilities and supervision. The research method used observational analytic with crossectional approach. Pololation of midwives implementing family planning services, the number of samples was 46 respondents from midwives who had implanted family planning services in family planning safeguards in health centers in Karawang regency, using purposive random sampling. Test analysis using Chi Square on the degree of significance Î±â‰¤0.05; confidence level (CI 95%) and Bynary Logistic Regression test for multivariable tests. The results showed good knowledge 63%, midwives attitude 54.3%, good infrastructure 63% and supervision 50%. There is a significant relationship between the availability of infrastructure (p = 0,000) and supervision (p = 0.003). The results of multivariable analysis showed that the infrastructure facilities had a significant influence on the behavior of midwives in applying standard precautions to implant contraceptive services in Karawang District (p = 0.05; (Exponent (B) = 20.77.) Keywords: midwives, standard precaution. implant services. Abstrak Salah satu upaya yang digunakan untuk peningkatan mutu pelayanan KB adalah dengan memastikan penggunaan standar pelayanan KB bagi petugas kesehatan termasuk pencegahan infeksi. Hasil SUSENAS 2015 menggambarkan tingginya pengguna Kontrasepsi modern MKJP sebesar 58.99% , dengan klinik KB Pemerintah sebagai fasilitas kesehatan yang memberikan pelayanan KB terbanyak sebesar 66,40%. Salah satu upaya untuk mendukung peningkatan pengguna kontrasepsi implan dan IUD di Kabupaten Karawang dilakukan salah satunya melalui kegiatan Safari KB Kabupaten. Tujuan penelitian untuk mengetahui determinan perilaku bidan dalam penerapann pencegahan infeksi dalam pelayanan kontrasepsi implan yang dilakukan pada kegiatan Safari KB, meliputi variabel pengetahuan, sikap, sarana prasarana dan supervisi. Metode penelitian menggunakan observasional analitik dengan pendekatan crossectional. Pololasi bidan pelaksana pelayanan KB, jumlah sampel sebanyak 46 responden bidan yang melakukan pelayanan KB implan pada kegiatan Safari KB di Puskesmas di Kabupaten Karawang, dengan cara purposive random sampling. Uji analisis menggunakan Chi Square pada derajat kemaknaan Î±â‰¤0,05; tingkat kepercayaan (CI 95% ) dan uji Bynary Logistic Regression untuk uji multivariabel. Hasil menunjukkan pengetahuan baik 63%, sikap bidan 54,3%, sarana prasarana baik 63% dan supervisi 50%. Ada hubungan bermakna antara ketersediaan sarana prasarana (p=0,000) dan supervisi (p=0,003). Hasil analisis multivariabel menunjukkan variabel sarana prasarana sangat berpengaruh terhadap perilaku bidan dalam penerapan kewaspadaan standar pada pelayanan kontrasepsi implan di Kabupaten Karawang (p=0,05; (Exponen (B)= 20,77.) Kata kunci: bidan,kewaspadaan standar,pelayanan implant.